2021
DOI: 10.1007/s11104-021-04854-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of carbon flow from grassland vegetation to soil microorganisms measured using 13C-labelling and signature fatty acids

Abstract: Purpose We investigated how the C flow from plants to microorganisms varies throughout the year in a temperate grassland. Additionally, we investigated how the C flow relates to saprotrophic activity and vegetation changes. Methods In situ stable isotope pulse labelling (13CO2) was employed to estimate the flow of recently plant-derived C to soil microorganisms by using signature fatty acids. Bacterial and fungal growth was estimated using radio-labelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
3
4
0
Order By: Relevance
“…Reference source not found.). This finding was supported by Birgander and Olsson (2021), who reported that the PLFA-13 C content in soil organic matter derived from saprophytic fungi was approximately six times higher than that derived from bacteria, indicating the superior ability of saprophytic fungi to acquire plant-derived C. Regarding grazing intensity, the value PLFA-13 C in SAP under HG was apparently higher than under MG and NG on the 60 th sampling day (Fig. 2B), probably driven by substantial root mortality caused by HG, which in turn triggered a significant proliferation of rhizosphere saprophytic fungi.…”
Section: Effects Of Grazing Intensity On Soil Microbessupporting
confidence: 57%
See 4 more Smart Citations
“…Reference source not found.). This finding was supported by Birgander and Olsson (2021), who reported that the PLFA-13 C content in soil organic matter derived from saprophytic fungi was approximately six times higher than that derived from bacteria, indicating the superior ability of saprophytic fungi to acquire plant-derived C. Regarding grazing intensity, the value PLFA-13 C in SAP under HG was apparently higher than under MG and NG on the 60 th sampling day (Fig. 2B), probably driven by substantial root mortality caused by HG, which in turn triggered a significant proliferation of rhizosphere saprophytic fungi.…”
Section: Effects Of Grazing Intensity On Soil Microbessupporting
confidence: 57%
“…Previous studies revealed that when considering the combination of PLFA relative abundance and 13 C enrichment ( 13 CCr), 13 CCr enabled better quantified the activity of soil microbes (Paterson et al, 2009;Balasooriya et al, 2013;Balasooriya et al, 2014;Balasooriya et al, 2016). Although the most previous studies had been proved that there were temporal patterns of rhizodeposit-C assimilating microbial communities in temperate ecosystems (Birgander and Olsson, 2021), in natural wetland (Balasooriya et al, 2013) and also in tropical paddy fields (Balasooriya et al, 2016), our studies found that different variations in soil microbial groups in alpine grassland (Fig. 3).…”
Section: Effects Of Grazing Intensity On Soil Microbesmentioning
confidence: 60%
See 3 more Smart Citations